Dehumanization Symbols in Stanley Kubrick’s A Clockwork Orange: An Analysis of Mask, Uniform, and Cane - Rama Syahrial Nugraha (PT. Alahyan Publisher Sukabumi, 2026)
Stanley Kubrick’s A Clockwork Orange (Kubrick, 1971) is a cinematic work celebrated for its distinct visual language, particularly the costumes and objects surrounding the protagonist, Alex DeLarge. While previous studies have extensively analyzed these elements through a Freudian lens as symbols of hyper-sexuality, this research argues that such interpretation is insufficient. This study aims to re-examine various visual artifacts and environmental symbols using Kennedy’s (X. J. Kennedy & Giola, 2005) theory to reveal their function in the process of dehumanization. The research utilizes a qualitative descriptive method with an objective approach, focusing on internal evidence found in the film. The data is collected through viewing and recording techniques. The findings demonstrate a shift in symbolic meaning: (1) The Costumes (Mask and Uniform) function as Action and Object Symbols for psychological dissociation; (2) The Accessories (Cane and Hat) serve as Symbols of Perverted Authority; (3) The Environmental Objects (Milk and Sculptures) reflect Total Objectification; and (4) The Prison Symbols reveal a shift to State Fascism. Collectively, these symbols do not merely represent aggression but function as a structured mechanism to strip away human empathy.